PENGUATAN QALBUN SALIM ANAK USIA DINI: MODEL INTERNALISASI NILAI KEJUJURAN DARI KISAH MUSA - Najmaddina; Mursalim; Muhammad Yusuf Qardlawi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the challenge of cultivating a sound moral-spiritual foundation (qalbun salim) in early childhood. It aims to develop a model for internalizing the value of honesty, derived from the story of Prophet Musa in the Quran, to strengthen qalbun salim. Employing qualitative library research with thematic interpretation (tafsir maudhu'i), the study synthesizes exegetical findings with pedagogical theories. The results construct a three-phase internalization model: (1) Narrative Engagement, introducing the story's ethical core; (2) Affective Connection, fostering emotional-spiritual reflection on honesty; and (3) Habitual Reinforcement, through activities embodying truthful behavior. The study concludes that the story of Musa offers a profound narrative framework for concretizing qalbun salim, advocating for the integration of such scripturally-based models into early childhood curricula to build a strong ethical foundation.